1985
DOI: 10.1111/1523-1747.ep12275490
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Antigens by Cultured Epithelial Cells: Comparison of Epidermis and Thymic Epithelium

Abstract: We have established long term in vitro cultures of human thymic epithelium and human epidermis free of contaminating fibroblasts. The cultured cells were examined using a panel of monoclonal antibodies which were raised against human thymic stroma and recognize tissue specific differentiation antigens of human epidermis and thymic epithelium. A subset of cultured epidermal cells (50%) and thymic epithelial cells (18%) expressed the TE-4 antigen characteristic of basal keratinocytes in skin and endocrine epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…TE cells were obtained by an explant technique using TE medium containing 67% DMEM (Life Technologies, Grand Island, NY), 22% Ham's F-12 (Life Technologies), 5% Fetal Clone II serum (HyClone, Logan, UT), 0.4 g/ml hydrocortisone, 5 g/ml insulin, 11 ng/ml recombinant human epidermal growth factor (Collaborative Biomedical, Bedford, MA), 0.18 M adenine, 10 溪10 M cholera toxin (ICN Biomedicals, Aurora, OH), 0.25 g/ml Fungizone, and 50 g/ml gentamicin on mitomycin-C-treated NIH-3T3 fibroblast feeder layers as described (23,24). Contaminating fibroblasts were removed from TE cultures by treatment with 0.02% EDTA in PBS followed by complement-mediated lysis with mAb 1B10, which binds to a cell surface Ag on fibroblasts (25).…”
Section: Te Monolayer and Organ Culturesmentioning
confidence: 99%
“…TE cells were obtained by an explant technique using TE medium containing 67% DMEM (Life Technologies, Grand Island, NY), 22% Ham's F-12 (Life Technologies), 5% Fetal Clone II serum (HyClone, Logan, UT), 0.4 g/ml hydrocortisone, 5 g/ml insulin, 11 ng/ml recombinant human epidermal growth factor (Collaborative Biomedical, Bedford, MA), 0.18 M adenine, 10 溪10 M cholera toxin (ICN Biomedicals, Aurora, OH), 0.25 g/ml Fungizone, and 50 g/ml gentamicin on mitomycin-C-treated NIH-3T3 fibroblast feeder layers as described (23,24). Contaminating fibroblasts were removed from TE cultures by treatment with 0.02% EDTA in PBS followed by complement-mediated lysis with mAb 1B10, which binds to a cell surface Ag on fibroblasts (25).…”
Section: Te Monolayer and Organ Culturesmentioning
confidence: 99%
“…In thymus, the function of the epithelium with regard to maturation (or education) of T cells may be related to its stage of differentiation. The data recently reported by Singer et al [7] demonstrated antigenic similarities beetween two groups of structures: on the one hand, the thymic epithelial network and the epidermal basal cell layer and on the other hand, HC and the suprabasal epidermal cell layer. Our results (table IV) obtained with a new panel of antithymic epithelium MCA, confirm these similarities between the two groups of struc tures.…”
Section: Discussionmentioning
confidence: 72%
“…Antigenic similarities have been revealed us ing various human and experimental anti bodies [2][3][4][5][6][7]. Recently, the heterogeneity of the thymic epithelial cells was documented on the basis of keratin polypeptide analysis [29,30] or tissue-specific differentiation an tigens identified by MCA [31,32], These an tibodies were used to define antigenic similarities between thymic epithelial cells and kcratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations